SYNTHESIS AND ANTIMICROBIALACTIVITYOF THIAZOlE DERIVATIVESCONTAINING TRIAZOlE MOIETYUSING Liar AS A CATALYST - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
ABSTRACT Synthesis of triazole derivatives from 2-mercaptobenzothiazole has been achieved in four steps under microwave irradiation. LiBr potentially replace solvents and corrosive acids in this reaction scheme. The products of triazole derivatives have shown antimicrobialactivity.